If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2y = ay Solving 3x + 2y = ay Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 3x + 2y + -2y = ay + -2y Combine like terms: 2y + -2y = 0 3x + 0 = ay + -2y 3x = ay + -2y Divide each side by '3'. x = 0.3333333333ay + -0.6666666667y Simplifying x = 0.3333333333ay + -0.6666666667y
| x/160=100/3 | | 6/9=n/1 | | 2/5x=55 | | 1.6x-3=1 | | 4-9X=39 | | 4/7x=63 | | 4x-(3x-15)=50 | | Y=4x^2+20x+9 | | y+2(4)=12 | | 12y=-34 | | x/60=14/15 | | 66+w=41 | | 7x/5-5=16 | | 7(v-9)=-7v-49 | | 7(5y-4)+2(4y+3)= | | T=14x^5+z | | 0.75x+8=-1 | | 0.75x+8=-8 | | y=e^2x/3 | | 3b+11= | | 8m=4(m+7) | | -16+76+135=0 | | -16t^2+76t+135=0 | | 5y+8+y= | | 2/f-19=-17 | | 1.06(50*0.65)=x | | V=3.14*3*3 | | V/60=17/20 | | 9-3x=1/2(4x-4) | | 5x+3y=3x+1y | | -6+13=2f+-11 | | (9x+17)=(5x+7) |